2022
DOI: 10.1038/s41598-022-19658-8
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond tunable solitons up to 4.8  µm using soliton self-frequency shift in an InF3 fiber

Abstract: A tunable ultrashort soliton pulse source reaching up to 4.8 µm is demonstrated based on a 2.8 µm femtosecond fiber laser coupled to a zirconium fluoride fiber amplifier followed by a small core indium fluoride fiber. This demonstration is extending by 300 nm the long wavelength limit previously reported with soliton self-frequency shift (SSFS) sources based on fluoride fibers. Our experimental and numerical investigation highlighted the spectral dynamics associated with the generation of highly redshifted pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In virtue of a befitting pump and fiber combination, it enables the laser wavelengths to be shifted towards our desired position within the fiber's transmission window. Along with the researches on physical mechanism, fiber materials and key techniques going deep, RFLs have advanced greatly in power raising [10,11], spectral quality improvement [12], wavelength extension [13,14] and so on. In MIR spectral region, a 3.7 W continuous wave (CW) fluoride glass RFL at 2.23 μm [11] and a quasi-CW chalcogenide glass RFL with the longest wavelength of 3.77 μm [13] have been reported respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In virtue of a befitting pump and fiber combination, it enables the laser wavelengths to be shifted towards our desired position within the fiber's transmission window. Along with the researches on physical mechanism, fiber materials and key techniques going deep, RFLs have advanced greatly in power raising [10,11], spectral quality improvement [12], wavelength extension [13,14] and so on. In MIR spectral region, a 3.7 W continuous wave (CW) fluoride glass RFL at 2.23 μm [11] and a quasi-CW chalcogenide glass RFL with the longest wavelength of 3.77 μm [13] have been reported respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In MIR spectral region, a 3.7 W continuous wave (CW) fluoride glass RFL at 2.23 μm [11] and a quasi-CW chalcogenide glass RFL with the longest wavelength of 3.77 μm [13] have been reported respectively. Gauthier et al demonstrated a tunable ultrafast pulse source reaching up to 4.8 μm [14], relying on a special SRS regime (soliton self-frequency shift) in InF3 fiber. These highlighted the great potential of the RFLs for developing the laser wavelength diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly the case when an Nth order soliton or mother soliton (MS) experiences fission and splits into N fundamental solitons, from which solitons of femtosecond duration typically emerge [1,13]. Exploiting the soliton fission mechanism for SSFS based wavelength conversion has been reported by different groups [14][15][16]. For example, Gauthier et al reported the soliton fission of a MS into solitons experiencing SSFS for wavelength conversion up to 4.8 m in InF3 fiber [14].…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting the soliton fission mechanism for SSFS based wavelength conversion has been reported by different groups [14][15][16]. For example, Gauthier et al reported the soliton fission of a MS into solitons experiencing SSFS for wavelength conversion up to 4.8 m in InF3 fiber [14]. Alamgir et al reported continuously tunable Raman solitons over the frequency range of 2.047-2.667 m using soliton fission and SSFS in an As2S3 microwire [16].…”
Section: Introductionmentioning
confidence: 99%
“…Higher-peak-power pulses, however, are difficult to generate from a mode-locked oscillator since pulse splitting will occur at high peak power in the fiber [19] . For scaling of peak power and pulse energy, several works on direct femtosecond pulse amplification accompanied with soliton self-compression [20][21][22][23][24] or soliton self-frequency shift (SSFS) [25][26][27][28] have been reported. Subtwo-cycle pulses with a peak power of approximately 500 kW have been realized through an Er-doped fluoride fiber amplifier and subsequent soliton self-compression [20] .…”
Section: Introductionmentioning
confidence: 99%